2020
DOI: 10.3390/ijerph17228622
|View full text |Cite
|
Sign up to set email alerts
|

Are Heated Tobacco Product Users Less Likely to Quit than Cigarette Smokers? Findings from THINK (Tobacco and Health IN Korea) Study

Abstract: Since the advent of heated tobacco products in June 2017 in South Korea, the sale of heated tobacco products accounted for 10.5% of total tobacco sales in 2019. However, the decreasing trend in total tobacco sales is gradually weakening and the number of visitors using stop smoking services has also dropped. This study examines the association between the use of new tobacco products and related products and cessation behaviors. A cross-sectional study using a self-administered questionnaire was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
(35 reference statements)
4
17
0
Order By: Relevance
“…Other emerging evidence is also ambiguous on this point, and the recent emergence of HTP precludes long-term follow up. On the contrary, cross-sectional evidence from South Korea has indicated a reduction in quitting among HTP users, while ecological analyses have pointed to a decline in visits to stop smoking clinics and a slowing in reductions of smoking rates [ 17 , 18 ]. Longitudinal research in Hong Kong has similarly not identified an increase in quit rates among HTP users [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Other emerging evidence is also ambiguous on this point, and the recent emergence of HTP precludes long-term follow up. On the contrary, cross-sectional evidence from South Korea has indicated a reduction in quitting among HTP users, while ecological analyses have pointed to a decline in visits to stop smoking clinics and a slowing in reductions of smoking rates [ 17 , 18 ]. Longitudinal research in Hong Kong has similarly not identified an increase in quit rates among HTP users [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the small sample size of some groups in the general population (e.g. dual users of e-cigarettes and HTPs), we targeted a convenience sample aged ≥19 years from March 2019 to July 2019 13 . For effective analysis, the minimum sampling number was set at 300 adults per group, excluding non-tobacco users.…”
Section: Methods Samplementioning
confidence: 99%
“…Still, they only discontinued CC and continued tobacco use by changing to EC or HTP. The reason can be explained by the misperception of safety that EC or HTP is safer or less harmful than CC, which was reported in Korean adults and young Americans 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Several questionnaires on EC and HTP asked abstinence on a 30-day basis. The definition came from the current smoking in adolescents,2 3 but it was also used in adult studies 25. Further discussion is needed on the question of EC, and HTP quit in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation